2008
DOI: 10.1038/cr.2008.282
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microRNAs in serum: a novel class of biomarkers for diagnosis of cancer and other diseases

Abstract: Dysregulated expression of microRNAs (miRNAs) in various tissues has been associated with a variety of diseases, including cancers. Here we demonstrate that miRNAs are present in the serum and plasma of humans and other animals such as mice, rats, bovine fetuses, calves, and horses. The levels of miRNAs in serum are stable, reproducible, and consistent among individuals of the same species. Employing Solexa, we sequenced all serum miRNAs of healthy Chinese subjects and found over 100 and 91 serum miRNAs in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
3,509
7
60

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 4,110 publications
(3,637 citation statements)
references
References 20 publications
61
3,509
7
60
Order By: Relevance
“…In the present study, we focused on cigarette smoking because it is a habit spread all over the world and is a significant risk factor for various diseases including cancer. In the present investigation of the plasma miRNA profiles of smokers and non-smokers, the subjects were limited to men because a study had reported subtle sex differences (Ji et al, 2009), although another study reported no large sex differences in plasma miRNA expression (Chen et al, 2008), and because smoking is more prevalent in men than in women in Japan. In addition, considering the potential effects of circadian rhythm (Shende et al, 2011), we standardized the time of blood collection.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focused on cigarette smoking because it is a habit spread all over the world and is a significant risk factor for various diseases including cancer. In the present investigation of the plasma miRNA profiles of smokers and non-smokers, the subjects were limited to men because a study had reported subtle sex differences (Ji et al, 2009), although another study reported no large sex differences in plasma miRNA expression (Chen et al, 2008), and because smoking is more prevalent in men than in women in Japan. In addition, considering the potential effects of circadian rhythm (Shende et al, 2011), we standardized the time of blood collection.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in prostate cancer, serum miR-141 level was found to distinguish metastatic prostate patients (n = 25) from age-matched controls [148]. Similarly, miR-25 and miR-223 were reported as non-small cell lung cancer specific following their analysis in sera from 152 patients compared to 75 healthy volunteers [149]. Circulating miRNAs, albeit in exosomes, have also been reported to have potential as biomarkers for ovarian cancer [150] and for glioblastoma [78].…”
Section: Micrornas In Breast Cancermentioning
confidence: 91%
“…Studies conducted by several research groups have confirmed the presence of miRNAs in various body fluids in humans, including serum [49][50][51], plasma [49,50], saliva [52], urine [53], milk [54], cerebrospinal fluid [55] and seminal fluid [56]. In cancer, there is a distinct relationship between the type of biological material and the original location of the neoplasm (e.g.…”
Section: Extracellular Mirnamentioning
confidence: 99%